Urbanization-driven Cladocera community shifts in the lake - a case study from Baltic region, Europe - Lanka, Anna; Dimante-Deimantovica, Inta; Saarni, Saija; Stivrins, Normunds; Tylmann, Wojciech; Zawiska, Izabela; Veski, Siim (Elsevier, 2025)
Our research aimed to evaluate, how urbanization affects lake ecosystems and Cladocera in particular. For this purpose, we chose a small urban lake with a well-documented history. Lake Velnezers (located in Riga, Latvia) is currently surrounded by apartment building complexes. Construction works around this lake started in the 1950s and continued up until the 1970s. To investigate how the transition from forested to agricultural and further urbanized land affected the lake ecosystem we took a sediment core that covers the time period from before 1875–2018. We evaluated ecological changes in the lake based on chemical and Cladocera species composition in sediment records and linked these changes to the historical information about alterations in the landscape around Velnezers. Our results show lake transitioned from oligotrophic to eutrophic conditions already before urbanization. The Lake ecosystem reacted to urbanization gradually, showing small changes in the beginning. However, in the 1980s lake experienced rapid deterioration in water quality – sediment records show an increase in heavy metal pollution, anoxia, and nutrient input. These stressors resulted in Cladocera functional group structure changes and loss of Cladocera species richness and diversity. Improvements in nature protection – such as wastewater management have reduced heavy metal and nutrient input into Lake Velnezers towards the present. However, previous deterioration, i.e. loss of species diversity and phosphorous legacy effect do not allow natural lake recovery under current conditions.